2019
DOI: 10.1002/jbm4.10224
|View full text |Cite
|
Sign up to set email alerts
|

Monosodium Glutamate Supplementation Improves Bone Status in Mice Under Moderate Protein Restriction

Abstract: Adequate protein intake during development is critical to ensure optimal bone gain and to attain a higher peak bone mass later. Using a mild protein restriction model in Balb/C mice consuming 6% of their total energy intake as soy protein (LP‐SOY)—for which we observed a significantly lower femoral cortical thickness, bone volume, trabecular number, and thickness reduction—we evaluated the effects of monosodium glutamate (MSG) supplementation at different concentrations (0.5, 1, 5, 10, and 20 g/kg of diet) on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…Thus, our data are in good accordance with the results of previous studies showing that a decrease in estrogen level is associated with central obesity, insulin resistance, and decreased energy expenditure ( [29][30]). As shown in previous experiments [11][12], LP diet reduced IGF-1 level. Our data show that bLF supplementation was able to increase several endocrine and physiological parameters, namely IGF-1 level, muscle mass, and muscle strength, thus once again supporting that bLF can increase protein synthesis in target tissues [31].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Thus, our data are in good accordance with the results of previous studies showing that a decrease in estrogen level is associated with central obesity, insulin resistance, and decreased energy expenditure ( [29][30]). As shown in previous experiments [11][12], LP diet reduced IGF-1 level. Our data show that bLF supplementation was able to increase several endocrine and physiological parameters, namely IGF-1 level, muscle mass, and muscle strength, thus once again supporting that bLF can increase protein synthesis in target tissues [31].…”
Section: Discussionsupporting
confidence: 85%
“…Therefore, osteoporosis is a major public health concern. We have previously shown in a model with mice fed a low protein diet (6% of total energy by soy protein) that this dietary condition reduces body weight associated with lower lean mass and BMD compared with mice receiving an adequate protein supply [11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Brakspear and Mason (2012) mentioned that Glu plays a role in bone formation and mass maintenance. Also, Blais et al (2019) found that increase in Gln plasma concentration stimulates osteoblast activity.…”
Section: Blood Parametersmentioning
confidence: 99%